Scientometric evaluation of the global research in acne disease - Khakimova, Aida; Zolotarev, Oleg; Senel, Engin (UI Scholars Hub, 2023)
Background: Although acne is one of the most common diseases, medical literature lacks a scientometric analysis relevant to this disorder. In the present study we aimed to perform a scientometric evaluation of literature related to acne. Methods: Publications were identified by searching for the term «acne» in PubMed. Papers from different countries were then identified by using the Advanced Search Builder. The indicators for evaluating of the absolute and relative increase in number of articles were proposed. Results: Dynamic publication of activity is compared according to our proposed indicator - The Average Relative Growth Rate. After 1945 an acceleration of the annual increase in articles was 2.7 times for acne, 1.3 times for acne vulgaris. For acne inversa, hidradenitis suppurativa, keloidal acne from 1985 the growth rate increased in 10-20 times. The other terms are characterized by a constant linear type of increase in publications. The United States has the most publications. Germany and the UK were in the second and third place. By the number of publications per million persons the leaders are Denmark, Israel, Georgia. The research productivity is weakly influenced by Gross Domestic Product. In developed countries the leaders are United States, Germany, Great Britain. In transition countries - China, Poland, Georgia. In developing countries - Turkey, India, Iran. Conclusion: Research activity in acne disease depends on the period of time and GDP of country. Such countries as Georgia, China, Turkey make an active contribution in acne research despite adverse socioeconomic factors.